On New Linear Operator Associated with Gaussian Hypergeometric Functions - Ahmed, Firas Ghanim; Darus, Maslina; Gaboury, Sebastien (Journal of Informatics and Mathematical Sciences, 2015)
In the present paper, we introduce new classes \(\sum_n^*(α,β,k,ρ)\) and \(\sum_n(α,β,k,ρ)\) of meromorphic functions dened by means of the linear operator \(L^* (α,β) f (z)\) for function in \({\mathbb U}^* =\{z:0 < |z| < 1\}\) and investigate a number of inclusion relationships of these classes. We also derive some interesting properties of these classes.